2009
DOI: 10.1016/j.jmb.2009.06.038
|View full text |Cite
|
Sign up to set email alerts
|

ATP Binding and Hydrolysis by Mcm2 Regulate DNA Binding by Mcm Complexes

Abstract: The essential minichromosome maintenance (Mcm)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“…This activity specifically requires the Mcm6/2 ATPase active site that was previously implicated as having a regulatory rather than a DNA-unwinding role in Mcm2-7 (32,68,69). Correspondingly, reference mcm alleles that do not affect the Mcm6/2 active site have apparently normal checkpoint signaling (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This activity specifically requires the Mcm6/2 ATPase active site that was previously implicated as having a regulatory rather than a DNA-unwinding role in Mcm2-7 (32,68,69). Correspondingly, reference mcm alleles that do not affect the Mcm6/2 active site have apparently normal checkpoint signaling (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…The Mcm6/2 active site biochemically functions to regulate rather than directly participate in DNA unwinding. Early work showed that a specific Mcm subcomplex (Mcm467) was competent to unwind DNA (71), while the addition of the remaining Mcm subunits (i.e., Mcm2, -3, and -5) inhibited this activity (69,72). In part, this inhibition depends upon conserved ATPase motifs in Mcm2 (i.e., the function of the Mcm6/2 active site) rather than altered oligomerization caused by Mcm2 binding to the Mcm467 subcomplex (69); mutations that reduce but do not eliminate ATP hydrolysis at this site are viable but demonstrate sensitivity to DNA-damaging agents, consistent with a potential checkpoint defect (68).…”
Section: Discussionmentioning
confidence: 99%
“…
Figure 6.ssDNA binding by Mcm2–7. ( A ) DNA binding was measured using a gel filtration-based assay (6). Binding of Mcm2 WT –7 (open triangle), Mcm2 EE –7 (filled square) and Mcm2 KR –7 (open circle) was determined in triplicate experiments and the mean plotted.
…”
Section: Resultsmentioning
confidence: 99%
“…These observations have led to the suggestion that Mcm2, 3 and 5 may play essential regulatory roles within Mcm2-7. Recent mutational studies are consistent with that idea [11,46]. However, the proposal that only a subset of Mcm2-7 subunits participates directly in DNA unwinding must be reconciled with studies on homohexameric helicases in which all subunits participate directly in the molecular mechanisms required for DNA translocation and DNA unwinding [6,56].…”
Section: Discussionmentioning
confidence: 95%